Eicosanoid mediator profiles in different phenotypes of nonsteroidal anti‐inflammatory drug‐induced urticaria. Issue 6 (6th February 2019) - Doña, Inmaculada; Jurado‐Escobar, Raquel; Perkins, James R.; Ayuso, Pedro; Plaza‐Serón, María Carmen; Pérez‐Sánchez, Natalia; Campo, Paloma; Bogas‐Herrera, Gador; Bartra, Joan; Torres, María José; Sanak, Marek; Cornejo‐García, José Antonio
Abstract: Background: The role of arachidonic acid metabolites in NSAID‐induced hypersensitivity has been studied in depth for NSAID‐exacerbated respiratory disease (NERD) and NSAID‐exacerbated cutaneous disease (NECD). However, no information is available for NSAID‐induced urticarial/angioedema (NIUA), despite it being the most frequent clinical entity induced by NSAID hypersensitivity. We evaluated changes in leukotriene and prostaglandin metabolites for NIUA patients, using patients with NECD and single‐NSAID‐induced urticaria/angioedema or anaphylaxis (SNIUAA) for comparison. Methods: Urine samples were taken from patients with confirmed NSAID‐induced urticaria and healthy controls, at baseline and at various time intervals after ASA administration. Eicosanoid measurement was performed using high‐performance liquid chromatography‐tandem mass spectrometry and gas chromatography‐mass spectrometry. Results: No differences were found between groups at baseline. Following ASA administration, LTE4 and 9α, 11β‐PGF2 levels were increased in both NIUA and NECD patients compared to baseline, rising initially, before decreasing toward initial levels. In addition, the levels of these metabolites were higher in NIUA and NECD when compared with the SNIUAA and control groups after ASA administration. No changes were found with respect to baseline values for SNIUAA and control groups. Conclusions: We present for the first time data regarding the role of COX‐1 inhibition in NIUA. Patients with this entity show a similar pattern eicosanoid levels following ASA challenge to those with NECD. Further studies will help ascertain the cell populations involved and the underlying molecular mechanisms. Abstract : The inhibition of COX‐1 by NSAIDs shunts the metabolism of arachidonic acid from PGE2 toward LTE4 synthesis. After NSAIDs intake, some individuals develop cutaneous and/or respiratory hypersensitivity reactions. Although NIUA and NECD showed distinct urinary eicosanoid excretion profile curves, ASA challenge results in an increase of LTE4 and 9a, 11b‐PGF2 in both. COX‐1: Cyclooxygenase 1; LTE4: Leukotriene E4; NECD: NSAIDs‐exacerbated cutaneous disease; NIUA: NSAIDs‐induced urticaria/angioedema; NSAIDs: Nonsteroidal anti‐inflammatory drugs; PGE2: Prostaglandin E2; 9a, 11b‐PGF2: 9α, 11β‐prostaglandin F2